Pengaruh Kompetensi Pegawai Terhadap Peningkatan Kualitas Pelayanan Publik di Kantor Pusat Universitas Sam Ratulangi Ma - Lumi, Djefry; Rares, Joyce J; Tulusan, Femmy M (JURNAL ILMIAH SOCIETY, 2015)
Sam Ratulangi University as one of the major universities are very concerned will be given public service employees, to the competence of the employees is a problem that is considered by the leadership, because without a good employee competence given the public service will not be maximized. The research methodology used is that while the survey is descriptive analytical method. The target population in this study is that there are employees in the Central Office and the University of Sam Ratulangi University Students Sam Ratulangi, with a total sample as many as 113. The data were analyzed by using multiple linear regression statistical correlation. From this study it can be concluded that Altogether employee competence, namely the concept of self (Self Concept), the competence of employees that employee knowledge and competence of the employees that employee skills a positive effect on improving the quality of public services in the Central Office of Sam Ratulangi University. Keywords: Employee Competence, Quality of Public Services